Respostas
respondido por:
1
equação ?
fazer analogia :
p =
p² =
A equação se torna
p² - 4p + 3 = 0
em seguida, o factor
(p - 1 ) (p - 3) = 0
p-1 = 0 ou p - 3 = 0
p= 1 ou p=3
p = 1
=
x = 0
ou
p = 3
=
x = 1
conclusão set : x = 0 e x = 1
saudações da Indonésia
fazer analogia :
p =
p² =
A equação se torna
p² - 4p + 3 = 0
em seguida, o factor
(p - 1 ) (p - 3) = 0
p-1 = 0 ou p - 3 = 0
p= 1 ou p=3
p = 1
=
x = 0
ou
p = 3
=
x = 1
conclusão set : x = 0 e x = 1
saudações da Indonésia
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás